Exploiting SLAs through Application of Economic Analysis on Datacenters’ Autonomic Management - Falcão, Eduardo Lucena; Cavalcante, Lucas Medeiros; Falcão, Rafael Vieira; Nunes, José Benardi Souza; Oliveira, Kaio Kassiano Moura; Brito, Andrey Monteiro (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2020: Anais do XXXVIII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2020)
Optimizing resource distribution in datacenters can achieve several economic benefits, including increasing energy efficiency, better workload performance, and higher levels of job acceptance. Although some studies propose strategies that increase resource utilization whilst meeting a certain QoS, there is a perspective yet to be exploited: the Service Level Agreements (SLA) amortization. We believe that keeping service levels far above the minimum agreed is a missed opportunity to apply more aggressive strategies to reduce allocated resource fragmentation and increase even further the benefits mentioned above. In this work, we propose a novel server rebalancing strategy based on economic systems, able to capitalize from the SLAs by keeping the harmony between the aggressive competition of Free Markets and the safe control of Regulated Markets. The proposed strategy is evaluated with a modified version of CloudSim Plus simulator. The outcomes show that the SLA exploitation strategy led to an economy of 8.6% up to 23% for different mechanism configuration.